CYTOTOXICITY OF JUSTICIA GENDARUSSA BURM F. LEAF EXTRACTS ON MOLT-4 CELL - Widiyanti, Prihartini; Prajogo, Bambang; Hikmawati, Ni Putu Ermi (Indonesian Journal of Tropical and Infectious Disease, 2016)
Justicia gendarussa Burm f. (Acanthaceae) is known for its activity as a male contraceptive and anti-HIV properties. The present study was designed to evaluate extracts of J. gendarussa for cytotoxicity activity against MOLT-4 cells. The cytotoxic activity of the fractionated-extract and 70% ethanol extracts of J. gendarussa leaves on MOLT-4 cells were evaluated using a WST-1 assay. The treatment cells, control cells without treatment and control media were also tested in duplicate. The absorbance was measured at a wavelength of 450 nm using a microplate absorbance reader (Bio-Rad). The average absorbance measures formazan produced by viable cells that metabolize the WST-1 reagent. Then the data was analyzed with regression analysis Microsoft Excel 2007 program to determine the concentration with 50% cell viability (50% Cytotoxicity Concentration, CC50). The CC50 values of the fractionated-extract and 70% ethanol extract of J. gendarussa leaves were 94 Î¼g/ml and 78 Î¼g/ml, respectively. The cytotoxicity of fractionated-extract and 70% ethanol extract of J. gendarussa leaves were not significantly different (p > 0.05). It can be concluded that the fractionated-extract and 70% ethanol extract of J. gendarussa leaves are not toxic to MOLT-4 cells.